2019
DOI: 10.1103/physrevb.100.235421
|View full text |Cite
|
Sign up to set email alerts
|

Near-field resonances in photon emission via interaction of electrons with coupled nanoparticles

Abstract: In this work we construct the first-principles theory for the near-field resonances arising in the system of two different coupled nanoparticles excited by the external field. The obtained expressions are valid for an arbitrary external field; the detailed analysis is performed for the case of a fast electron passing by. The energy of electron is arbitrary, so the results are valid both for relativistic and nonrelativistic electrons. We have obtained rigorous analytical solution for the radiation field and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…Note that all the theory developed here does suppose that the single particles composing the array do not interact. This approximation holds true when the distance between them significantly exceeds their sizes; see [24].…”
Section: Radiation Field and Intensitymentioning
confidence: 98%
“…Note that all the theory developed here does suppose that the single particles composing the array do not interact. This approximation holds true when the distance between them significantly exceeds their sizes; see [24].…”
Section: Radiation Field and Intensitymentioning
confidence: 98%
“…where E act is the total field acting on a microparticle. Following the approach outlined in [14], we obtain the i-th component of the field at long distances in form (4) where δ is is the Kronecker symbol, k is the wave-vector, is the Fourier image of the s-component of the field of the electron at point : (5) , and (6) and we used the notations:…”
Section: Diffraction Radiation From a Cluster Of Two Particlesmentioning
confidence: 99%
“…In recent years, a series of studies appeared in which the authors investigated SPR from singleperiod gratings with simultaneous excitation of surface plasmons, which significantly enhance the radiation [12,13]. In [14], on an example of a cluster of two particles, it was shown that radiation enhancement is possible not only due to the excitation of plasmons on the surface of such structures, but also due to the interaction between elements. The interaction effect manifests itself in the shift in radiation frequencies, splitting of maxima, and the appearance of new intensity maxima.…”
Section: Introductionmentioning
confidence: 99%
“…В случае отсутствия взаимодействия между частицами (элементами) мишени решение задачи об излучении кластера сводится к решению одночастичной задачи, с учетом лишь набега фаз для волн от соседних частиц. Однако, как показано ранее [8], в процессе поляризационного излучения учет взаимодействия между частицами может быть весьма существен, вести к новым эффектам в картине излучения, в том числе к резонансному усилению, изменению положения пиков наибольшей интенсивности. В этом случае эффект взаимодействия между элементами кластера приводит к необходимости решать систему взаимосвязанных уравнений, что резко усложняет поиск решения даже для достаточно небольшого числа частиц в кластере.…”
unclassified
“…Вычислим поле излучения с учетом взаимодействия всех частиц. В системе двух частиц учет взаимодействия был выполнен в работе [8]. Неравенство R 0 << λ позволяет воспользоваться для расчета дипольным приближением.…”
unclassified